High-efficiency hybrid trim method for CFD simulation of rigid coaxial rotor. (January 2023) - Qi, Haotian; Wang, Ping; Jiang, Linsong; Zhang, Yang; Wang, Liangquan
In order to solve the trim problem of computational fluid dynamics (CFD) simulation for rigid coaxial rotor, a hybrid trim model coupling CFD method and high-efficiency model (blade element theory) is established. In the trim process, the Jacobian matrix is solved by the high-efficiency model, while the CFD solver is only called for rotor performances modifying after each trimming step. The influences of pseudo time step, number of CFD revolution, and inflow model are investigated. Validation cases of AH-1G and Harrington-1 rotors are carried out, and good agreements are obtained. Results show that the trim efficiency can be significantly improved by saving the calculation of CFD for the Jacobian matrix. The trim accuracy is guaranteed by the correction operation with the CFD solver at each step. Moreover, as only time-averaged rotor performances are useful for trim, the efficiency can be further improved by adopting appropriately small pseudo time step and CFD revolution. The hybrid trim model has high robustness. The accuracy of inflow model for the coaxial rotor affects the convergence speed, but the final convergence can be achieved generally.